Strategi Pembelajaran Full Day School Dalam Penguatan Penerapan Nilai Keislaman Peserta Didik di SD Muhammadiyah Muara Bungo - Amin, Muhammad; Winata, Widia (Information Technology Education Department, 2025)
This study examines the learning strategies of full day school in strengthening the implementation of Islamic values among students at SD Muhammadiyah Muara Bungo. Using a qualitative method, data were collected through interviews, observations, and documentation studies involving the principal, teachers, and students of SD Muhammadiyah Muara Bungo.The results show that the implementation of the full day school learning system at SD Muhammadiyah Muara Bungo runs effectively and consistently, employing an integrated system strategy within the curriculum, school management, classroom learning, extracurricular activities, and life skills programs. The Islamic values emphasized include obedience to Allah SWT and His Messenger, love for the Qur’an, good manners, sincerity, love of knowledge, honesty, discipline, and responsibility, which are strengthened through agreement, exemplary behavior, and habituation methods. Reinforcement is further achieved by assigning independent tasks at home.